PPJB Power of Attorney to Sell: Validity, Land Rights Registration, and Normative Gaps Under Indonesian Law - Maudy Fadhilah (jfpublisher, 2026)
The Sale and Purchase Binding Agreement (PPJB) has become a prevalent instrument in Indonesian land transactions; however, the legal standing of the power of attorney to sell embedded within it remains contested in practice. The specific point of contestation concerns the boundary between a prohibited absolute power of attorney under the Instruction of the Minister of Home Affairs Number 14 of 1982, which bans its use as a covert mechanism for transferring land rights, and a lawful irrevocable power of attorney that is accessory to a fully paid PPJB. A further unresolved problem concerns the legal mechanism by which final and binding court decisions may serve as the basis for land rights registration at the National Land Agency (BPN), particularly where the PPJB and power of attorney mechanism has failed due to the seller's non-cooperation. This study employs normative legal research through statutory and conceptual approaches, drawing on primary, secondary, and tertiary legal materials. The study establishes five cumulative conditions for the legal validity of the power of attorney to sell within a fully paid PPJB, grounded in Articles 1320, 1792, and 1796 of the Civil Code and the applicable agrarian regulations. It further concludes that the BPN's obligation to implement a final court decision ordering land rights registration is ministerial rather than discretionary, and that any refusal constitutes an ultra vires act subject to challenge before the State Administrative Court. The study also identifies the court-appointed power of attorney as a significant normative gap in Indonesian positive law and proposes concrete legislative and regulatory interventions to strengthen legal certainty in Indonesian land transactions.